Capsaicinoids, Chloropicrin and Sulfur Mustard: Possibilities for Exposure Biomarkers - Pesonen, Maija; Vähäkangas, Kirsi; Halme, Mia; Vanninen, Paula; Seulanto, Heikki; Hemmilä, Matti; Pasanen, Markku; Kuitunen, Tapio (Frontiers in Pharmacology, 2010)
Incapacitating and irritating agents produce temporary disability persisting for hours to days after the exposure. One can be exposed to these agents occupationally in industrial or other working environments. Also general public can be exposed in special circumstances, like industrial accidents or riots. Incapacitating and irritating agents discussed in this review are chloropicrin and capsaicinoids. In addition, we include sulfur mustard, which is an old chemical warfare agent and known to cause severe long-lasting injuries or even death. Chloropicrin that was used as a warfare agent in the World War I is currently used mainly as a pesticide. Capsaicinoids, components of hot pepper plants, are used by police and other law enforcement personnel as riot control agents. Toxicity of these chemicals is associated particularly with the respiratory tract, eyes and skin. Their acute effects are relatively well known but the knowledge of putative long-term effects is almost non-existent. Also, mechanisms of effects at cellular level are not fully understood. There is a need for further research to get better idea of health risks, particularly of long-term and low-level exposures to these chemicals. For this, exposure biomarkers are essential. Validated exposure biomarkers for capsaicinoids, chloropicrin and sulfur mustard do not exist so far. Metabolites and macromolecular adducts have been suggested biomarkers for sulfur mustard and these can already be measured qualitatively, but quantitative biomarkers await further development and validation. The purpose of this review is, based on the existing mechanistic and toxicokinetic information, to shed light on the possibilities for developing biomarkers for exposure biomonitoring of these compounds. It is also of interest to find ideas for early effect biomarkers considering the need for studies on subchronic and chronic toxicity.